The Optimal Degree of Polarization - Ioulia V. Ossokina; Otto Swank (Tinbergen Institute, 2001)
In the literature on electoral politics full convergence of policy platforms is usually regarded as socially optimal. Thereason is that risk-averse voters prefer a sure middle-of-the-road policy to a lottery of two extremes with the sameexpectation. In this paper we study the normative implications of convergence in a simple model of electoralcompetition, in which parties are uncertain about voters' preferences. We show that if political parties haveincomplete information about voters' preferences, the voters may prefer some degree of policy divergence. Theintuition is that policy divergence enables voters to correct policies that are based on a wrong perception of theirdesires.
Keywords: D72; 330; Elections; Policy divergence; Probabilistic voting; Voters' preferences; Wahlverhalten; Ökonomische Theorie der Demokratie; Theorie; Politische Willensbildung